Effect Of Feeding Formaldehyde Treated Groundnut Cake On Growth Performance Of Barbari Kids - Singh, V.P.; Nayak, S.; Baghel, R.P.S.; Gupta, R.S.; Patil , A.K.; Khare , A. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
An experiment was conducted on 14 barbari goat kids to evaluate the effect of protected ground nut cake (GNC) on performance of growing kids for 90 days. In treatment T1 (control) kids were given untreated GNC on growth performance Significant (P
Keywords: Formaldehyde treated GNC; growth performance; barbari kids